Grupos reflexivos com homens autores de violências como instrumento de enfrentamento à violência de gênero - Albuquerque, Esdras Ferreira (2022)
The approach to reflexive group with men who are perpetrators of violence concerns an ethical-political commitment founded with the aim of breaking with gender violence. It consists in considering man within a relational perspective, in which his figure is indispensable for the construction of an effective public policy for the end of violence against women, through the process of resignification of the behavior of men who are perpetrators of violence. In this sense, the present research has as general objective to analyze gender violence in the light of the actions with men who perpetrate violence against women. Therefore, this is a qualitative research developed through the documental analysis of three documents of the reflective group "Project Reflect". From the structural and composition perspective of the program, we used the "project opening form" responsible for the creation and specification of their respective practices, justifications, objectives, target audience, agencies involved, description of the activities and factors and risks of the respective proposal. Under the effectiveness/results aspect of practices, the "Project Results Report between 2018 (year of its creation) until 2022 was analyzed", as well as the "Report of the activities developed in the 'Reflect Project' from the Specific Supervised Internship I of the year 2019", from the institutional perspective (who executes the project; responsible promoter; facilitators responsible; period of realization, total workshops, number of participants; and age group, total evasion and recidivism numbers) and practical (description of activities and organization of results by facilitators in supervised internship). To complement the data, we applied an open questionnaire with the coordinator of the reflective group and another with the responsible (s) responsible for the development of group activities, aiming to understand how the performance unveiled in the "Reflect Project" works in practice and correlate the information in the documents and statements, with what has been discussed in the literature about reflective groups. The analysis of the results was based on the documental analysis model developed by Cellard (2008), from four perspectives: Structure, activities and dynamics developed, organization and results achieved, and group action. Moreover, the need for an effective public policy in the fight against gender-based violence permeates the use of gender-based reflective groups as an instrument to further the construction of this policy of deconstruction of hierarchies. However, as relevant as the performance of the "Reflect Project" is, it has a theoretical and practical construction focused on psychological aspects and not from a gender perspective, even if it takes certain core concepts. It is therefore incapable of intending the intricacies of gender-based violence.